Authentic perception of gender in the Pomor ethnic group in the pages of S. Maximov's book "The Year in the North" (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the expression of gender issue in the ethnographic work of S.V. Maximov "The Year in the North", analyzes the speech patterns, dialect vocabulary and conversations with residents of Arkhangelsk province, wich are documented there, illustratively shows that the perception of gender in the Pomor ethnic group  differs from the standard Russian perception, though it coincides with it partly.
Keywords: gender; speech patterns; pomors; authenticity; estimated vocabulary